2012
DOI: 10.1103/physrevx.2.011014
|View full text |Cite
|
Sign up to set email alerts
|

A Waveguide-Coupled On-Chip Single-Photon Source

Abstract: We investigate single-photon generation from individual self-assembled InGaAs quantum dots coupled to the guided optical mode of a GaAs photonic crystal waveguide. By performing confocal microscopy measurements on single dots positioned within the waveguide, we locate their positions with a precision better than 0:5 m. Time-resolved photoluminescence and photon autocorrelation measurements are used to prove the single-photon character of the emission into the propagating waveguide mode. The results obtained de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
183
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(185 citation statements)
references
References 40 publications
2
183
0
Order By: Relevance
“…The use of III-V materials, especially GaAs and InP compounds, is very promising for QPIC [3] because it allows the integration of on-demand single-photon sources. Semiconductor quantum dots (QDs) have been shown to be nearly ideal sources of non-classical light [4] that can be efficiently routed into nanophotonic circuits [5][6][7][8]. As compared to integrated single-photon sources based on parametric processes in LiNbO 3 [9] or Si waveguides [10], QDs offer the advantage of much higher efficiency and easier filtering of the pump beam.…”
Section: Introductionmentioning
confidence: 99%
“…The use of III-V materials, especially GaAs and InP compounds, is very promising for QPIC [3] because it allows the integration of on-demand single-photon sources. Semiconductor quantum dots (QDs) have been shown to be nearly ideal sources of non-classical light [4] that can be efficiently routed into nanophotonic circuits [5][6][7][8]. As compared to integrated single-photon sources based on parametric processes in LiNbO 3 [9] or Si waveguides [10], QDs offer the advantage of much higher efficiency and easier filtering of the pump beam.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the integration of QDs in photonic circuits, in particular photonic crystal waveguides, [16][17][18][19][20][21] which extended the use of these emitters as integrated in-plane quantum light sources.…”
mentioning
confidence: 99%
“…However, in the emerging field of photonic quantum information technology, it is highly desirable for the integrated quantum emitter to be able to emit highly indistinguishable photons into an on-chip quantum circuit. The integration of QDs in photonic circuits, in particular photonic crystal waveguides (PCWGs), [21][22][23][24][25][26][27] has extended the use of these emitters as integrated in-plane quantum light sources. These systems offer broadband operation, 20 efficiency 23,28 and scalability.…”
mentioning
confidence: 99%